Genome-wide identification of cyclic nucleotide-gated channel gene family in Solanum tuberosum and silencing of StCNGC2 provides resistance to Pectobacterium carotovorum - Sun, Kaile; Liu, Shuai; Mao, Huipo; Zha, Qianqian; Liu, Han; Shen, Shunshan; Jacobsen, Evert; Visser, Richard G. F.; Bai, Yuling; Li, Chengwei; Jia, Zhiqi; Meng, Geng; et al. (Frontiers in Plant Science, 2025)
Cyclic nucleotide-gated ion channel (CNGC) genes play vital roles in plant growth, development, and responses to both biotic and abiotic stresses. However, the current research on CNGCs in potato (Solanum tuberosum) remain largely uncharacterized. Blackleg disease is one of the most devastating diseases worldwide, causing severe yield losses. Understanding the role of the StCNGC gene family in blackleg resistance is therefore of significant importance. In this study, we identified 11 StCNGC genes in the potato genome and conducted phylogenetic analysis, gene structure characterization, and conserved motif prediction. Expression patterns were examined in different tissues and under stress conditions. The identified StCNGCs were classified into five groups, and showed conserved gene structures and motifs within groups. Most StCNGCs were induced under biotic stress conditions. Notably, silencing StCNGC2 conferred resistance to blackleg disease and resulted in the upregulation the pathogenesis-related marker gene StPR1. Together, these findings suggest that StCNGC2 plays a crucial role in potato defense against blackleg disease and provide a foundation for further functional studies of the StCNGC gene family.